USE OF SCRAMBLE LEARNING MODEL TO INCREASE STUDENTS' READING INTEREST IN INDONESIAN LANGUAGE SUBJECTS GRADE V STUDENTS AT SD NEGERI GUNONG KLENG MEUREUBO SUBDISTRICT - Jurna Runibar (Sensei International Journal of Education and Linguistic, 2021)
This study aims to determine the increase in students' reading interest by using the scramble learning model in SD Negeri Gunung Keling, Meureubo District. This type of research is classroom action research. The subjects in this study were 21 students. The data collection techniques are through tests of student learning outcomes, student activity observation sheets, teacher activity observation sheets and questionnaires. The conclusion of this research is "The use of scramble model can increase students' reading interest in Indonesian language subject for fifth grade students of SD Negeri Gunung Keling, Meureubo District. This is evidenced by the increase in the percentage of students' reading interest in each cycle, in the pre-cycle implementation the majority of students' reading interest scores are still below the KKM with the percentage of completeness only 61.90%, while in cycle I the results of students' reading interest have increased but not maximally, namely 80, 95% after the implementation of cycle II the results of students' reading interest became better, where the percentage of the number of students who completed reached 90.47% of the total number of students.